2018
DOI: 10.1177/1468017318794280
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of empathy in women social workers

Abstract: Summary This study explored the manifestation of reflective ability, emotional intelligence and empathy in 120 women social workers in Tiruchirappalli, India. A cross-sectional quantitative design was used and the Emotional Intelligence Scale, Groningen Reflective Ability Scale and the Empathy Assessment Index were administered to assess the manifestation of these dimensions. Multiple regression analysis was used to identify predictors of empathy. Findings Based on mean scores, the majority of respondents were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 63 publications
3
12
0
4
Order By: Relevance
“…Similarly, interacting and knowing the vulnerability of Rajan's parents (more vulnerable) made him more empathetic, and increase his connection with the society at large. This fits with the findings from a previous study that highlighted this argument-sharing and expressing emotions (and vulnerabilities) could make people more empathetic [60]. Such increased social empathy could also be a positive response to the pandemic (and lockdown).…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, interacting and knowing the vulnerability of Rajan's parents (more vulnerable) made him more empathetic, and increase his connection with the society at large. This fits with the findings from a previous study that highlighted this argument-sharing and expressing emotions (and vulnerabilities) could make people more empathetic [60]. Such increased social empathy could also be a positive response to the pandemic (and lockdown).…”
Section: Discussionsupporting
confidence: 90%
“…Teaching techniques and classroom methodologies familiarize social workers to empathetic skills [55]. In a study, among social work students, the results suggest that empathetic modeling from professors and field supervisors enhance social work students' empathy.…”
Section: Factors That Influence Empathymentioning
confidence: 93%
“…Age, self-reflection, appraisal, and emotions' expressions were associated with women's social workers empathy. Social workers had a higher score of empathy whenever they had previous work experience [55]. Additionally, there are studies that support that being female is associated with higher levels of empathy [56,57].…”
Section: Factors That Influence Empathymentioning
confidence: 94%
See 1 more Smart Citation
“…Zewdie, Tsion, Mirkuzie, & Sudhakar [31] reported that being minority is a significant predictor of empathy while gender is not. Age is also reported as a significant predictor of the empathy, which may stand for grade level in this study, in Stanley, Buvaneswari, & Meenakshi's [32] studies which aimed to identify predictors of empathy in women social workers [28].…”
Section: Discussionmentioning
confidence: 64%